All-cause mortality following low-dose aspirin treatment for patients with high cardiovascular risk in remote Australian Aboriginal communities: an observational study. Issue 1 (2nd January 2020) - Zhao, Yuejen; Jeyaraman, Kanakamani; Burgess, Paul; Connors, Christine; Guthridge, Steven; Maple-Brown, Louise; Falhammar, Henrik
Abstract : Objectives: To evaluate the benefit and risk of low-dose acetylsalicylic acid (aspirin) in patients from remote Aboriginal communities in the Northern Territory, Australia. Design: Retrospective cohort study using primary care and hospital data routinely used for healthcare. Aspirin users and non-users were compared before and after controlling confounders by matching. Marginal structural models (MSM) were applied to ascertain the benefit and risk. Setting: The benefit and harm of aspirin were investigated in patients aged ≥18 years from 54 remote Aboriginal communities. Participants: None had a previous cardiovascular event or major bleeds. Patients on anticoagulants or other antiplatelets were excluded. Intervention: Aspirin at a dose of 75–162 mg/day. Outcome measures: Endpoints were all-cause, cardiovascular mortality and incidences of cardiovascular events and major bleeds. Results: 8167 predominantly Aboriginal adults were included and followed between July 2009 and June 2017 (aspirin users n=1865, non-users n=6302, mean follow-up 4 years with hospitalisations 6.4 per person). Univariate analysis found material differences in demographics, prevalence of chronic diseases and outcome measures between aspirin users and non-users before matching. After matching, aspirin was significantly associated with reduced all-cause mortality (HR=0.45: 95% CI 0.34 to 0.60; p<0.001), but not bleeding (HR=1.13: 95% CI 0.39 to 3.26; p=0.820). After using MSMs to eliminate the effects of confounders, loss of follow-up and time dependency of treatment, aspirin was associated with reduced all-cause mortality (HR=0.60: 95% CI 0.47 to 0.76; p<0.001), independent of age (HR=1.06; p<0.001), presence of diabetes (HR=1.42; p<0.001), hypertension (HR=1.61; p<0.001) and alcohol abuse (HR=1.81; p<0.001). No association between aspirin and major bleeding was found (HR=1.14: 95% CI 0.48 to 2.73; p=0.765). Sensitivity analysis suggested these findings were unlikely to have been the result of unmeasured confounding. Conclusion: Aspirin was associated with reduced all-cause mortality. Bleeding risk was less compared with survival benefits. Aspirin should be considered for primary prevention in Aboriginal people with high cardiovascular risk.